Onsite Sewage Treatment and Disposal Systems: Viruses - Mary Lusk; Gurpal S. Toor; Thomas Obreza (EDIS)
Keeping disease-causing microorganisms out of groundwater used for drinking water supplies is important to protect human health. This 7-page fact sheet characterizes the behavior of viruses in septic systems and the soil drain field and summarizes what we know about the extent and character of groundwater contamination with viruses emanating from septic systems. Written by Mary Lusk, Gurpal S. Toor, and Tom Obreza, and published by the UF Department of Soil and Water Science, October 2011.